Six Weeks of Low-Load Blood Flow Restricted and High-Load Resistance Exercise Training Produce Similar Increases in Cumulative Myofibrillar Protein Synthesis and Ribosomal Biogenesis in Healthy Males - Sieljacks, Peter; Wang, Jakob; Groennebaek, Thomas; Rindom, Emil; Jakobsgaard, Jesper Emil; Herskind, Jon; Gravholt, Anders; Møller, Andreas B.; Musci, Robert V.; de Paoli, Frank V.; Hamilton, Karyn L.; Miller, Benjamin F.; et al. (Frontiers in Physiology, 2019)
Purpose: High-load resistance exercise contributes to maintenance of muscle mass, muscle protein quality, and contractile function by stimulation of muscle protein synthesis (MPS), hypertrophy and strength gains. However, high loading may not be feasible in several clinical populations. Low-load blood flow restricted resistance exercise (BFRRE) may provide an alternative approach. However, the long-term protein synthetic response to BFRRE is unknown and the myocellular adaptations to prolonged BFRRE are not well-described. Methods: To investigate this, 34 healthy young subjects were randomized to 6 weeks of either low-load BFRRE, HLRE, or non-exercise control (CON). Deuterium oxide (D2O) was orally administered throughout the intervention period. Muscle biopsies from m. vastus lateralis were collected before and after the 6-week intervention to assess long-term myofibrillar MPS and RNA synthesis as well as muscle fiber-type specific cross-sectional area (CSA), satellite cell content, and myonuclei content. Muscle biopsies were also collected in the immediate hours following single-bout exercise to assess signaling for muscle protein degradation. Isometric and dynamic quadriceps muscle strength was evaluated before and after the intervention. Results: Myofibrillar MPS was higher in BFRRE (1.34 %/day, p < 0.01) and HLRE (1.12 %/day, p < 0.05) compared to CON (0.96 %/day) with no significant differences between exercise groups. Muscle RNA synthesis was higher in BFRRE (0.65 %/day, p < 0.001) and HLRE (0.55 %/day, p < 0.01) compared to CON (0.38 %/day) and both training groups increased RNA content, indicating ribosomal biogenesis in response to exercise. BFRRE and HLRE both activated muscle degradation signaling. Muscle strength increased 6-10 % in BFRRE (p < 0.05) and 13-23 % in HLRE (p < 0.01). Dynamic muscle strength increased to a greater extent in HLRE (p < 0.05). No changes in type I and type II muscle fiber-type specific CSA, satellite cell content, or myonuclei content were observed. Conclusions: These results demonstrate that BFRRE increases long-term muscle protein turnover, ribosomal biogenesis, and muscle strength to a similar degree as HLRE. These findings emphasize the potential application of low-load BFRRE to stimulate muscle protein turnover and increase muscle function in clinical populations where high loading is untenable.